Photopolymers: beyond the standard approach to photosensitisation - Naydenova Izabela; Martin Suzanne; Toal Vincent (Journal of the European Optical Society-Rapid Publications, 2009)
A photopolymerizable material for use in the visible normally consists of a dye sensitizer, a free radical generator, monomer/monomers and, optionally, a binder, and is prepared usually as a dry or liquid film. Upon illumination with light of appropriate wavelength, a photopolymerisation reaction is triggered, leading to a change in the film’s refractive index. Because the presence of the dye is essential, the film is usually made sensitive to light during its preparation. Here we separate the film preparation and the sensitisation processes. In this way the photopolymerisation process can be used to detect dye labelled analytes, providing an alternative to fluorescence detection methods that offers visual, easy to interpret information. Our approach also allows for a precise control of the spatial location of the photoinduced refractive index changes that can be utilised for holography, lithography and photonic device fabrication.